Alterations and correlations in dental plaque microbial communities and metabolome characteristics in patients with caries, periodontitis, and comorbid diseases - Ying Wang; Fei Yang; Yuan Wang; Shuli Deng; Rui Zhu (BMC, 2024)
Abstract Backgrounds The pathogenic microorganisms and clinical manifestations of caries and periodontitis are different, caries and periodontitis are usually discussed separately, and the relationship between them is ignored. Clinically, patients prone to dental caries generally have a healthier periodontal status, whereas patients with periodontitis generally have a lower incidence of dental caries. The relationship between dental caries and periodontitis remains unclear. Objectives This study aimed to explain the clinical phenomenon of antagonism between dental caries and periodontitis by exploring the ecological chain and bacterial interactions in dental caries, periodontitis, and other comorbid diseases. Methods The dental plaque microbiomes of 30 patients with oral diseases (10 each with caries, periodontitis, and comorbid diseases) were sequenced and analysed using 16 S rRNA gene sequencing. The Kyoto Encyclopaedia of Genes and Genomes (KEGG) database was used for a differential functional analysis of dental plaque microbial communities in caries, periodontitis, and comorbid diseases. Results The coinfection group had the greatest bacterial richness in dental plaque. The principal coordinate analysis showed that caries and periodontitis were separate from each other, and comorbid diseases were located at the overlap of caries and periodontitis, with most of them being periodontitis. Simultaneously, we compared the microbiomes with significant differences among the three groups and the correlations between the microbiome samples. In addition, KEGG pathway analysis revealed significant differences in functional changes among the three groups. Conclusions This study revealed the composition of the dental plaque microbial communities in caries, periodontitis, and comorbidities and the differences among the three. Additionally, we identified a possible antagonism between periodontitis and caries. We identified a new treatment strategy for the prediction and diagnosis of caries and periodontitis.